88.0k views
3 votes
Solve for x
-5(-2-5)-x-1=-12

User Apotry
by
5.4k points

2 Answers

4 votes

Answer:

46

Explanation:

-5(-2-5)-x-1=-12

-5(-7)-x-1=- 12

35 - x - 1 = -12

34 - x = -12

-x = -12 - (-34)

-x = - 46

x = 46

User Sumedh Tambat
by
4.6k points
4 votes

Answer:


x=46

Explanation:


-5\left(-2-5\right)-x-1=-12

⟹ Subtract -2 and 5 = -7


  • 5\left(-2-5\right)

  • 5\left(-7\right)

⟹ Remover parentheses:


  • 5*7

  • -35


-\left(-35\right)-x-1=-12

⟹ Apply rule:
-\left(-a\right)=a


35-x-1=-12

⟹ Combine like terms:


  • -x+35-1=-12

  • \:35-1=34

  • -x+34=-12

⟹ Subtract 34 from both sides:


  • -x+34-34=-12-34

  • -x=-46

⟹ Divide both sides by -1:


  • (-x)/(-1)=(-46)/(-1)

  • x=46

___________________

OAmalOHopeO

___________________

User CoronA
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.